Evaluation of an intensive education program on the treatment of tobacco-use disorder for pharmacists: a study protocol for a randomized controlled trial - El Hajj, Maguy Saffouh; Awaisu, Ahmed Awaisu; Kheir, Nadir; Nik Mohamed, Mohamad Haniki; Haddad, Rula Shami; Ahmed Saleh, Rana; Mohammed Alhamad, Noora; Mohd Almulla, Ahmad; Mahfoud, Ziyad R. (BioMed Central Ltd, 2019)
Background: Tobacco use is presently responsible for the death of over seven million people across the world. In Qatar, it is one of the main causes of premature deaths and preventable diseases. To reduce tobacco use, Qatar has ratified the World Health Organization (WHO)’s Framework Convention on Tobacco Control (FCTC) and has implemented many tobacco-control initiatives. In spite of these measures, tobacco use is still considered a public health threat in Qatar. Pharmacists practicing in retail/community pharmacy settings are often the first port of call for individuals requiring general health advice. Evidence has proven that they have a pivotal role in health promotion and disease prevention including tobacco cessation. However, pharmacists in Qatar are not actively involved in tobacco control and many have not received any education or training about smoking cessation counseling in the past. In an effort to build the capacity of pharmacists towards tobacco control in Qatar, the aim of the proposed study is to design, implement, and evaluate an intensive education program on tobacco dependence treatment for pharmacists in Qatar. Methods/design: The study will be a prospective randomized controlled trial comparing an intensive tobacco-related education program versus non-tobacco-related training on pharmacists’ tobacco-use-related knowledge, attitudes, selfefficacy, and skills. Community pharmacists practicing in Qatar will be eligible for participation in the study. A random sample of pharmacists will be selected for participation. Consenting participants will be randomly allocated to intervention or control groups. Participants in the intervention group will receive an intensive education program delivered by a multi-disciplinary group of educators, researchers, and clinicians with expertise in tobacco cessation. A short didactic session on a non-tobacco-related topic will be delivered to pharmacists in the control group. The study has two primary outcomes: post-intervention tobacco-related knowledge and post-intervention skills for tobacco cessation assessed using a multiple-choice-based evaluation instrument and an Objective Structured Clinical Examination (OSCE), respectively. The secondary study outcomes are post-intervention attitudes towards tobacco cessation and selfefficacy in tobacco-cessation interventions assessed using a survey instrument. An additional secondary study outcome is the post-intervention performance difference in relation to tobacco-cessation skills in the practice setting assessed using the simulated client approach. Discussion: If demonstrated to be effective, this education program will be considered as a model that Qatar and the Middle East region can apply to overcome the burden of tobacco-use disorder. Trial registration: ClinicalTrials.gov, ID: NCT03518476. Registered on 8 May 2018. Version 1/22 June 2018.